The EDC3 chronology for the EPICA Dome C ice core - F. Parrenin; J.-M. Barnola; J. Beer; T. Blunier; E. Castellano; J. Chappellaz; G. Dreyfus; H. Fischer; S. Fujita; J. Jouzel; K. Kawamura; B. Lemieux-Dudon; et al. (Copernicus Publications, 2007)
The EPICA (European Project for Ice Coring in Antarctica) Dome C drilling in East Antarctica has now been completed to a depth of 3260 m, at only a few meters above bedrock. Here we present the new EDC3 chronology, which is based on the use of 1) a snow accumulation and mechanical flow model, and 2) a set of independent age markers along the core. These are obtained by pattern matching of recorded parameters to either absolutely dated paleoclimatic records, or to insolation variations. We show that this new time scale is in excellent agreement with the Dome Fuji and Vostok ice core time scales back to 100 kyr within 1 kyr. Discrepancies larger than 3 kyr arise during MIS 5.4, 5.5 and 6, which points to anomalies in either snow accumulation or mechanical flow during these time periods. We estimate that EDC3 gives accurate event durations within 20% (2σ) back to MIS11 and accurate absolute ages with a maximum uncertainty of 6 kyr back to 800 kyr.